AN EXAMINATION OF SOCIOLOGICAL AND PSYCHOLOGICAL PERSPECTIVES ON SUICIDE THROUGH THE WORKS OF EMILE DURKHEIM AND ZYGMUNT BAUMAN - Shukurova Sabokhat Odilovna (American Journals Publishing, 2024)
This article delves into the profound and multifaceted theme of suicide as explored through the foundational theories of Émile Durkheim and the contemporary insights of Zygmunt Bauman. Suicide, as a critical social issue, has garnered attention across various disciplines, necessitating an interdisciplinary approach to fully grasp its complexities. By examining Durkheim's empirical analysis of social factors influencing suicidal behavior, including his pioneering typology of suicide—egoistic, altruistic, anomic, and fatalistic—this study elucidates the essential role that societal integration and regulation play in shaping individual experiences of despair.
Keywords: Suicide, Émile Durkheim, Zygmunt Bauman, social integration, modernity, existential despair, sociological analysis, psychological factors, community support, individualization, mental health, public health, consumerism, identity crises, social cohesion, qualitative research, interdisciplinary approach, cultural context, societal structures, mental well-being.